Moderate water depth effects on the response of a floating wind turbine - Zhang, Lixian; Michailides, Constantine; Wang, Yapo; Shi, Wei (My University, 2020)
In the present paper, the mooring lines system of the V-shaped floating wind turbine (VSWT) at 50-m water depth is designed accounting shoaling effects and fully coupled aero-hydro-servo-elastic effects. The motions and mooring line tension responses under different load cases are analyzed at moderate water depth and are compared with revelant responses at deeper water depths for highlighting the rational response of the VSWT in shallow waters. The responses are dominated mainly by wave actions for the parked condition, while by wind actions for operational conditions. Moreover, comparisons between the onshore wind turbine (WT), monopile WT at 30-m water depth and VSWT at 50-m water depth are presented for different response and performance quantities including the generator power output and structural internal loads in order to study the rationality and efficiency of the mooring line design at moderate water depths and compare responses with alternative competitive possible solutions. It is found that the standard deviation of the generator power of the VSWT is larger than that of the onshore WT and monopile WT due to large platform motions induced by hydrodynamic loads. Moreover, the hydrodynamic loads on the VSWT have a great impact on the tower base loads, while do not significantly affect the rotor thrust force and blade root force. The results presented in the paper proves the efficient design of the VSWT at moderate water depths ready for use.
Keywords: Moderate water depths; Fully coupled analysis; Floating offshore wind turbines; Hydrodynamic loads; Mooring system design